2020
DOI: 10.1016/j.marenvres.2020.105126
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and sorbed contaminants – Trophic exposure in fish sensitive early life stages

Abstract: The present study evaluated very small microplastic particle (MPs) transfer to zebrafish and marine medaka larvae via prey experimentally exposed to MPs from the onset of feeding. Larvae were fed Paramecium or Artemia nauplii loaded with fluorescent 1-5 or 10-20 μm MP. Pollutant accumulation was analyzed by optically tracking of benzo [a]pyrene (BaP) and recording cyp1a transcription. Paramecium transferred 1-5 μm particles only, whereas Artemia efficiently transferred both MPs. Although zebrafish and medaka l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…This is consistent with high rates of ingestion of both microplastic colors by brine shrimp (see “ Results ” section) and the idea that brine shrimp nauplii are fairly indiscriminate eaters. Other studies have shown that ingestion of nanoplastics and microplastics by zooplankton is common (Cole et al 2013 ; Desforges et al 2015 ; Sun et al 2017 ; Cousin et al 2020 ), and that retention of microplastics is fairly low (Wang et al 2019 ), zooplankton as a group may be particularly susceptible to the negative effects of microplastic pollution. It is becoming increasingly clear that microplastics may be transferred up the food web (e.g., Setälä et al 2014 ; Cousin et al 2020 ; Hasegawa and Nakaoka 2021 ; Stienbarger et al 2021 ), more studies of the ecological effects of trophic transfer are needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with high rates of ingestion of both microplastic colors by brine shrimp (see “ Results ” section) and the idea that brine shrimp nauplii are fairly indiscriminate eaters. Other studies have shown that ingestion of nanoplastics and microplastics by zooplankton is common (Cole et al 2013 ; Desforges et al 2015 ; Sun et al 2017 ; Cousin et al 2020 ), and that retention of microplastics is fairly low (Wang et al 2019 ), zooplankton as a group may be particularly susceptible to the negative effects of microplastic pollution. It is becoming increasingly clear that microplastics may be transferred up the food web (e.g., Setälä et al 2014 ; Cousin et al 2020 ; Hasegawa and Nakaoka 2021 ; Stienbarger et al 2021 ), more studies of the ecological effects of trophic transfer are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that ingestion of nanoplastics and microplastics by zooplankton is common (Cole et al 2013 ; Desforges et al 2015 ; Sun et al 2017 ; Cousin et al 2020 ), and that retention of microplastics is fairly low (Wang et al 2019 ), zooplankton as a group may be particularly susceptible to the negative effects of microplastic pollution. It is becoming increasingly clear that microplastics may be transferred up the food web (e.g., Setälä et al 2014 ; Cousin et al 2020 ; Hasegawa and Nakaoka 2021 ; Stienbarger et al 2021 ), more studies of the ecological effects of trophic transfer are needed. Our study found immediate effects on growth and a trend toward greater mortality when larval fish consume zooplankton that have ingested microplastics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to physical stress afforded by the ingestion of MPs resulting in laceration, inflammation processes and starvation, impacts are also devoted to the intake of additive or sorbed hazardous chemical contaminants adsorbed onto MPs’ surface, thus becoming a carrier for transporting and releasing substances in marine organisms [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%